Molecular Pathways Underlying Projection Neuron Production and Migration during Cerebral Cortical Development - Ohtaka-Maruyama, Chiaki; Okado, Haruo (Frontiers in Neuroscience, 2015)
Glutamatergic neurons of the mammalian cerebral cortex originate from the radial glia (RG) progenitors in the ventricular zone (VZ). During corticogenesis, neuroblasts migrate toward the pial surface using two different migration modes. One is multipolar (MP) migration with random directional movement, and the other is locomotion, which is a unidirectional movement guided by the RG fiber. After reaching their final destination, the neurons finalize their migration by terminal translocation, which is followed by maturation via dendrite extension to initiate synaptogenesis and thereby complete neural circuit formation. This switching of migration modes during cortical development is unique in mammals, which suggests that the RG-guided locomotion mode may contribute to the evolution of the mammalian neocortical 6-layer structure. Many factors have been reported to be involved in the regulation of this radial neuronal migration process. In general, the radial migration can be largely divided into four steps; (1) maintenance and departure from the VZ of neural progenitor cells, (2) MP migration and transition to bipolar cells, (3) RG-guided locomotion, and (4) terminal translocation and dendrite maturation. Among these, many different gene mutations or knockdown effects have resulted in failure of the MP to bipolar transition (step 2), suggesting that it is a critical step, particularly in radial migration. Moreover, this transition occurs at the subplate layer. In this review, we summarize recent advances in our understanding of the molecular mechanisms underlying each of these steps. Finally, we discuss the evolutionary aspects of neuronal migration in corticogenesis.